Understanding, Acceptance, and Habituation of Pancasila Behavior from the Implementation of the Pancasila P5 Student Profile Strengthening Project on Global Cooperation and Diversity at SMA Negeri 4 Singaraja - Yulia, Komang Yulia Purnama Yanti; Sukadi, Sukadi; Budiarta, I Wayan (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2025)
Abstract This study examines the implementation of the Pancasila Student Profile Strengthening Project (P5) with a focus on global diversity at SMA Negeri 4 Singaraja, Bali, using a descriptive qualitative approach with a case study design. Data was collected through interviews, observations, document analysis, and focus group discussions to explore the planning process, teacher and student perceptions, and instilled values about global diversity. The findings show that the POACR (Planning, Organizing, Mobilizing, Controlling, Reflecting) strategy supports activities such as cultural video analysis, watching collective films on diversity, and interviews with resource persons, improving students' understanding of "Bhinneka Tunggal Ika". Teachers and students provide positive feedback, although challenges such as time constraints and student motivation are addressed through WhatsApp communication and mentoring. The values of tolerance, cooperation, and acceptance of differences are instilled through student presentations and essays. The research offers practical insights for schools and academic contributions to the Independent Curriculum, with recommendations for multi-site and longitudinal studies.  Keywords: Pancasila Student Profile Strengthening Project, global diversity, Bhinneka Tunggal Ika.